2013
DOI: 10.1088/1009-0630/15/1/07
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the Anti-Felting Properties of Sputtered Wool Using Plasma Treatment

Abstract: In this research the effects of mordant and plasma sputtering treatments on the crystallinity and morphological properties of wool fabrics were investigated. The felting behavior of the treated samples was also studied. We used madder as a natural dye and copper sulfate as a metal mordant. We also used copper as the electrode material in a DC magnetron plasma sputtering device. The anti-felting properties of the wool samples before and after dying was studied, and it was shown that the shrink resistance and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The durability of this kind of treatment is questionable and also may affect the handle properties of the treated fabric but the developed treatment is eco-friendly. Borghei et al investigated DC magnetron sputter coating of wool with copper and found that 1 min treatment was enough to make wool shrink-resist [107].…”
Section: Subtractive Treatments Based On Partial/full Removal Of Cutimentioning
confidence: 99%
“…The durability of this kind of treatment is questionable and also may affect the handle properties of the treated fabric but the developed treatment is eco-friendly. Borghei et al investigated DC magnetron sputter coating of wool with copper and found that 1 min treatment was enough to make wool shrink-resist [107].…”
Section: Subtractive Treatments Based On Partial/full Removal Of Cutimentioning
confidence: 99%
“…After 5 washing cycles, unmodified and dyed Clevios F ET wool became lighter (L 57.49), light blue (h 107.15), yellowish (b* 6.16), less green (a* −1.89), but with more saturated color (C 3.98). The untreated wool fabrics may have felted and shrunk during washing, which may have increased the color deposition, thus being the reason for the higher saturated color result [44]. The measured CIE L * a * b * C * h coordinates and K/S values at the maximum wavelength of 520 nm are presented in Table 5.…”
Section: Spectrophotometric Measurements Of Color Intensitymentioning
confidence: 99%
“…Furthermore, the protease mainly acts on the cell membrane complex (CMC) between surface scale and cortical cells, causing serious damage to the fiber strength. 7 To improve the effect of protease, methods such as multi-enzyme synergy, [8][9][10] ultrasonic treatment, 11 plasma radiation, 12 and chitosan pre-adsorption 2 were used to increase the effect of protease on the surface scale, and reduce the damage to the fibers. 13,14 However, the ultrasonic and plasma technologies limited by equipment are difficult to apply in industry, and the chemical reagents will seriously affect the feel and strength of the fabric.…”
Section: Introductionmentioning
confidence: 99%